Approaches To Assessing the Level of Innovation Potential Industrial Enterprise in Russian Practice - Natalia Viacheslavovna VASILIEVA; Evgeniy Alekseyevich IVANOV; Andrey Evgenievich MAKUSHEV; Ekaterina Vasilievna AGAEVA (Communications of International Proceedings, 2021)
The present article is concerned with approaches to determining innovation potential of an enterprise, analyzes its structure in terms of its main components, considers methods for assessing the level of innovative potential of the industrial enterprise, and evaluates innovative potential of the machine-building enterprise based on an integral approach.
Keywords: sustainable development of the enterprise; innovation activity; innovation potential; structure of innovation potential.